Hairiness Values of the Polyester/Viscose Ring-Spun Yarn Blends - (:unkn) unknown (INST CHEMICAL FIBRES, 2008)
In this work, 0.133 - 0.166 tex and 38 mm of fiber length of polyester and viscose rovings of 591 tex (a,, 8) were blended variously (polyester/viscose 35/65%; polyester/viscose 50/50%; polyester/viscose 65/35%; polyester 100% and viscose 100%) and the yarns were produced at spindle speed of 18000 rev/min with 48 mm of ring diameter and C type of traveller 50 mg (No. 1/0) in ring frames. Later the resulted 20 tex yarns were examined by measuring its tenacity, elongation, irregularity and hairiness. The aim of this study is to investigate the hairiness of ring-spun polyester/viscose blends, which are commonly used in the textile industry, by using three different test methods. The pilling values of these produced samples were also determined. The outcomes have been assessed according to the blend ratios and fiber locations which were scanned on the scanning electron microscope; the observations were concluded both on the hairiness and pilling values depending on the blend proportions. As a result, within the produced yarns the worse hairiness was obtained on the viscose (100%) yarns and the worse pilling values were existed on the knitted fabrics which are formed from these spun yarns.
Keywords: polyester; viscose; blends; ring-spun yarn properties; hairiness; pilling; TRAVELER WEIGHT; COTTON YARNS